Blucher Design Proceedings 2020
DOI: 10.5151/sigradi2020-74
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous parametric process for daylight simulation applied to the proposal of a daylighting of buildings performance tool

Abstract: The openings features definition, considering the obstructions influence caused by the urban environment, are extremely relevant for the daylit buildings design. The complexity of the daylight phenomenon and the need to estimate its performance spread the use of parametric simulation and simulation programs. Thus, this article aims to create a parametric process, derived from a digital process, capable of simulating and registering the performance of daytime construction in different urban scenarios in an auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…The parametric process was consolidated in five steps: four regarding the programming operation and, one regarding the validation of its results. Details about the autonomous parametric process, developed for this study, can be found in (Mariano et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The parametric process was consolidated in five steps: four regarding the programming operation and, one regarding the validation of its results. Details about the autonomous parametric process, developed for this study, can be found in (Mariano et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…O processo completo é dividido em quatro grandes etapas já descritas em trabalhos como Mariano (2018), Mariano et al (2020) e Mariano e Pereira (2020), sendo: Ambiente, Escolha, Organização e Simulação. Estes quatro passos definem uma base geral para o processo, criando um traçado de ações que resultam na formação e avaliação dos elementos de fachada com características fractais.…”
Section: Desenvolvimento Do Processo Paramétrico E Generativounclassified
“…A fim de entender e aplicar o processo paramétrico e generativo computacional foram pesquisados os seguintes conceitos: características fractais; processos digitais de projeto; simulações; e comportamento da luz do dia. Na sequência foram desenvolvidas as diferentes etapas do processo paramétrico por intermédio do Grasshopper, uma plataforma de programação visual, seguindo etapas já consolidadas em trabalhos como Mariano (2018), Mariano et al (2020) e Mariano e Pereira (2020). Tal estrutura possibilita que o processo digital desenvolva elementos de fachada, potencialize esses componentes, organize-os em uma composição e avalie a consequente distribuição da luz do dia.…”
Section: Introductionunclassified